Characteristics of Teaching Community Capital - Focus on Teachers in Reformed Public Education Institutions - Pusztai, Gabriella; Morvai, Laura; Bacskai, Katinka; Hornyák, Agnes (Central European Journal of Educational Research, 2020)
The issue of the effectiveness of teaching is constantly at the center of research. "Teachers count", presents the OECD report (2005), which confirms the research of the day that the work of the teacher contributes significantly to the performance of students. The question is how to capture the factors that influence school performance. The focus of the examination of the theoretical background is on the professional capital theory, with the emphasis on the examination of social / teaching capital in addition to the human capital and decision capital components. Our research is based on a secondary analysis of a questionnaire among teachers working in Calvinist institutions in 2017. The focus of our interest is on identifying the characteristics (frequency) and content (agreeing with norms) of staff capital and the need for teachers to develop collaborative networking opportunities for future professional development.